2018
DOI: 10.31348/2018/6/5
|View full text |Cite
|
Sign up to set email alerts
|

Silent Sinus Syndrome

Abstract: Silent sinus syndrome je vzácné, pomalu se rozvíjející onemocnění spojené s asymptomatickou chronickou maxilární sinusitidou s následným vtažením spodiny očnice směrem dolů. K očním projevům patří enophtalmus, hypoglobus, pseudo-retrakce horních víček a pseudo-Graefeho příznak. Diagnosticky je nepřínosnější CT vyšetření orbity a paranasálních dutin. Léčba spočívá v provedení endoskopické antrostomie, případně v rekonstrukci dna orbity. Po operaci dochází ke znovuobnovení ventilace čelistní dutiny a k úpravě oč… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…From this review, clinical outcomes of sinusitis seemed difficult to find when compared with radiological outcomes [27], which is a critical point considering the greater evidence of radiological signs [7] that can cause silent sinusitis with otorhinolaryngological consequences, both chronically and over time [44,45]. Indeed, both symptomatic and silent sinusitis were taken into account in this review to extend the analysis to the evaluation of sinusitis diagnosis (nasal endoscopy and radiological assessment) and treatment (FESS vs. simple antibiotic vs. follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…From this review, clinical outcomes of sinusitis seemed difficult to find when compared with radiological outcomes [27], which is a critical point considering the greater evidence of radiological signs [7] that can cause silent sinusitis with otorhinolaryngological consequences, both chronically and over time [44,45]. Indeed, both symptomatic and silent sinusitis were taken into account in this review to extend the analysis to the evaluation of sinusitis diagnosis (nasal endoscopy and radiological assessment) and treatment (FESS vs. simple antibiotic vs. follow-up).…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] In previously reported CMA cases, the maxillary sinus infundibulum was shown to be obstructed on CT.[ 4 ] In addition, they were often associated with conditions likely to cause occlusion of the maxillary infundibulum, such as lateralisation of the uncinate process and middle turbinate, enlargement of the ipsilateral middle meatus and ipsilateral septal deviation to the affected sinus. [ 2 , 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Initially, there was the hypothesis that it was linked with hypoplasia of the maxillary [8]. This theory proved to be inconsistent after several studies showed normal sinus anatomy many years before the onset of symptoms, which favors that CMA is an acquired and progressive condition [9].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only patient 3 had mild enophthalmos. Another possible finding is retraction of the upper eyelid and Graefe's pseudo-sign, which is the illusion of the lack of convergence of the upper eyelids when looking down due to unilteral hypoglobus [9]. Stage III CMA may also have these manifestations, so as sinonasal symptoms.…”
Section: Discussionmentioning
confidence: 99%